Method for obtaining large-area flexible perovskite battery thin film without stress damage

By using a thermally detached double-sided adhesive film and perovskite precursor to prepare films on a flexible substrate and heated to remove stress-free damage, the problem of stress damage during removal of flexible perovskite battery film is solved, and an efficient and simplified preparation process and high-performance film are achieved.

CN119654041APending Publication Date: 2025-03-18ANHUI LINGZHONG NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411752869.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is easy to cause stress damage when removing the flexible perovskite battery film from the hard glass, which affects the performance of the film.

Method used

The thermally detached double-sided adhesive film is used to paste the non-thermal detached adhesive surface on the hard glass, and the flexible substrate is pasted on the thermally detached adhesive surface. The film is prepared on the flexible substrate by using perovskite precursor liquid, and the thermally detached adhesive surface is lost to its viscosity by heating, so as to achieve removal without stress damage.

Benefits of technology

It effectively avoids stress damage, simplifies the preparation process, reduces costs, and ensures high performance of large-area flexible perovskite battery films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654041A_ABST
    Figure CN119654041A_ABST
Patent Text Reader

Abstract

The invention provides a method for obtaining a large-area flexible perovskite battery thin film without stress damage. The method comprises the following steps: selecting a proper thermal viscosity loss double-sided adhesive film; adhering a non-thermal-loss adhesive surface of the thermal-loss double-sided adhesive film to the hard glass substrate; adhering the flexible substrate to the heat loss adhesive surface of the heat loss adhesive film; the preparation method comprises the following steps: dissolving AX and BX2 in N, N-dimethylformamide according to a stoichiometric ratio of 1: 1 to obtain a perovskite precursor solution; preparing a perovskite cell thin film on a flexible substrate by using the perovskite precursor solution; and heating the whole perovskite cell thin film, heating the thermal viscosity loss adhesive surface of the thermal viscosity loss double-sided adhesive film to lose viscosity, and taking down the perovskite cell thin film from the hard glass substrate. The thermal viscosity loss adhesive surface of the thermal viscosity loss double-sided adhesive film can lose viscosity through heating, so that the perovskite cell thin film can be automatically separated from the hard glass substrate, stress damage caused by bending, tearing and taking down the perovskite thin film is avoided, and the operation is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a method for obtaining a large-area flexible perovskite battery film without stress damage. Background Art

[0002] Perovskite solar cells have become a research focus due to their advantages such as low cost and high photoelectric conversion efficiency. With the development of science and technology, the demand for flexible, bendable and wearable electronic products is growing. Flexible perovskite solar cells can provide convenient energy supply for these products, so they have broad application prospects in the fields of military, aerospace, consumer electronics, etc.

[0003] Since a single flexible substrate is not conducive to the preparation of perovskite battery films, the currently widely used solution is to stick the flexible substrate onto hard glass. However, when the prepared flexible perovskite battery film is removed from the hard glass, the bending and tearing process will cause irreversible stress damage to the perovskite battery film, resulting in a decrease in the performance of the final prepared perovskite battery.

[0004] Therefore, there is an urgent need for a simple and effective method that can remove flexible perovskite battery films from hard glass without stress damage. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a simple and effective method for obtaining a large-area flexible perovskite battery film without stress damage. The large-area flexible perovskite battery film prepared based on this method can be removed from hard glass without being damaged by stress.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] A method for obtaining a large-area flexible perovskite battery film without stress damage comprises the following steps:

[0008] (1) According to the annealing temperature required for the perovskite, a suitable thermally debonded double-sided adhesive film is selected; the thermally debonded double-sided adhesive film includes two adhesive surfaces: a thermally debonded adhesive surface and a non-thermal debonded adhesive surface (a common adhesive surface that is not easily affected by temperature);

[0009] (2) adhering the non-thermal debonding adhesive surface of the thermal debonding double-sided adhesive film to a hard glass substrate;

[0010] (3) pasting the flexible substrate onto the heat-loss adhesive surface of the heat-loss adhesive film;

[0011] (4) dissolving AX and BX2 in N,N-dimethylformamide at a stoichiometric ratio of 1:1 to obtain a perovskite precursor solution;

[0012] (5) Preparing a perovskite battery film on a flexible substrate using the prepared perovskite precursor solution;

[0013] (6) The entire prepared perovskite battery film is heated, and the heat-debonding adhesive surface of the heat-debonding double-sided adhesive film loses its adhesiveness due to the heat, and the perovskite battery film is removed from the hard glass substrate.

[0014] As one of the preferred embodiments of the present invention, in step (1), the selection criteria of the thermal debonding double-sided adhesive film is: the thermal debonding temperature of the thermal debonding adhesive surface is higher than the annealing temperature required for perovskite.

[0015] As one of the preferred embodiments of the present invention, the heat-debonding double-sided adhesive film includes the following according to its debonding mechanism:

[0016] Foaming type: It will decompose or react at high temperature to release gas (such as nitrogen, carbon dioxide, etc.) and expand to form foam, increase the volume, reduce the density, resulting in reduced adhesion, thus achieving loss of adhesion. Its ingredients are usually high temperature resistant polymers, such as silicone resin or polyurethane, combined with high temperature decomposition foaming agents, such as azodicarbonamide, sodium bicarbonate, etc.

[0017] Thermal cracking type: reduces viscosity by thermal cracking or degradation at high temperature. When the temperature reaches a certain value, the colloid structure undergoes chemical decomposition, the viscosity is greatly reduced, and thus the viscosity is lost. Its ingredients usually contain some polymer substrates that are easily decomposed at high temperatures, such as polyurethane, polyimide, etc.

[0018] Thermal release type: It only loses viscosity at high temperature without structural changes. It mainly relies on different proportions of functional cross-linking agents and thermal de-viscosity aids to achieve de-viscosity. Its ingredients are usually silane coupling agent (de-viscosity aid) and azobisisobutyronitrile (functional cross-linking agent).

[0019] Phase change type: This type of adhesive undergoes a physical phase change (such as melting) at high temperatures, changing from a solid state to a liquid state or a state with significantly reduced viscosity. After cooling, it usually does not restore its original viscosity and eventually loses viscosity. Its common ingredients mainly include polyacrylate, polyethylene, polyvinyl chloride, etc.

[0020] Microcapsule type: This type of viscosity-losing adhesive contains active ingredients in microcapsules. The microcapsules rupture at high temperatures, releasing the viscosity-losing agent or reacting chemically, resulting in a decrease in the viscosity of the colloid. Its main ingredients include microcapsules that rupture at high temperatures, and the microcapsules contain oily ingredients or special solvents.

[0021] The heat-debonding double-sided adhesive film of the present invention is preferably a foaming type commonly used in the market, and the heat-debonding temperature of the heat-debonding adhesive surface thereof is 90-150° C., and the debonding heating time is 3-5 min.

[0022] As one of the preferred embodiments of the present invention, in the step (3), the flexible substrate is one of ITO-PEN, ITO-PET, and ITO-PI conductive films.

[0023] As one of the preferred embodiments of the present invention, in step (4), A is one or more of formamidinium ion, methylamine ion, and cesium ion; B is one or more of lead ion, tin ion, manganese ion, germanium ion, and copper ion; and X is one or more of chloride ion, iodide ion, and bromide ion.

[0024] As one of the preferred embodiments of the present invention, in step (5), a spin coating method is used to prepare a large-area perovskite battery film.

[0025] As one of the preferred methods of the present invention, the specific operation of preparing a large-area perovskite battery film by spin coating is as follows:

[0026] Before spin coating: Use UV-ozone instrument to treat for 20-30 minutes to improve the wettability of the flexible substrate so that the perovskite precursor solution can be evenly spin-coated in the subsequent spin coating step;

[0027] Spin coating: evenly drop the prepared perovskite precursor solution on the flexible substrate, set the rotation speed to 5000-6000rpm, and the duration is 3-9s to obtain a uniformly dispersed perovskite wet film;

[0028] After spin coating: use a flash evaporator to extract the solvent in the wet film, and then anneal the extracted film at a temperature of 85 to 145° C. for 5 to 60 minutes to obtain a perovskite battery film.

[0029] As one of the preferred embodiments of the present invention, in the step (6), the entire prepared perovskite battery film is placed on a heating table, and the heating temperature is set to be 5 to 10°C higher than the thermal debonding critical temperature of the thermal debonding double-sided adhesive film; the thermal debonding adhesive surface of the thermal debonding double-sided adhesive film loses its viscosity after being heated, and the perovskite film together with the flexible substrate is removed from the hard glass substrate, thereby obtaining the desired large-area flexible perovskite battery film.

[0030] The advantages of the present invention compared to the prior art are:

[0031] (1) The heat-debonding adhesive surface of the heat-debonding double-sided adhesive film of the present invention can lose its stickiness by heating after the perovskite annealing and crystallization is completed, and the flexible substrate and the perovskite battery film thereon can automatically detach from the hard glass substrate; this method can avoid the ordinary double-sided adhesive film from being too firmly adhered, which causes stress damage when the perovskite film is bent and torn to be removed;

[0032] (2) The heat-detack double-sided adhesive film of the present invention loses its stickiness after being heated for 3 to 5 minutes, thus avoiding the influence of high temperature on the perovskite battery film;

[0033] (3) The method of the present invention is easy to operate, simplifies the preparation process of perovskite battery thin film, and reduces costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the bonding structure between the heat-debonding double-sided adhesive film and the hard glass substrate and the flexible substrate in Examples 1 to 3;

[0035] Figure 2 It is a schematic diagram of the operation of preparing a perovskite battery film by spin coating in Examples 1 to 3 (in the figure, Figure a is spin coating of a perovskite precursor solution; Figure b is flash evaporation; Figure c is annealing of a perovskite battery film);

[0036] Figure 3 It is a schematic diagram of removing a large-area flexible perovskite battery film without stress damage in Examples 1 to 3;

[0037] Figure 4 This is the effect of the thermally debonded double-sided adhesive film and ordinary double-sided adhesive on the perovskite battery film in Experimental Example 1 (in the figure, Figure a is the interface state of the perovskite battery film after peeling off the ordinary double-sided adhesive; Figure b is the interface state of the perovskite battery film after peeling off the thermally debonded double-sided adhesive film). DETAILED DESCRIPTION

[0038] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments. At the same time, the reagents, materials and experimental methods used in the following embodiments are conventional reagents, materials and methods in the art unless otherwise specified, and will not be repeated.

[0039] Example 1

[0040] A method for obtaining a large-area flexible FAPbI3 perovskite battery film without stress damage in this embodiment includes the following steps:

[0041] (1) Clean a 4.5 cm × 4.5 cm hard glass substrate to facilitate the firm adhesion of the heat-debonding double-sided adhesive film.

[0042] (2) Prepare a heat-debonding double-sided adhesive film of the same size (Kunshan Dongzhimei Electronics Co., Ltd., foamed thermal peelable film, product number DZM-2, 90°C heating temperature); the heat-debonding double-sided adhesive film includes a heat-debonding adhesive surface and a non-heat-debonding adhesive surface, the heat-debonding temperature of the heat-debonding adhesive surface is 90°C, and the debonding heating time is 3 minutes.

[0043] (3)Reference Figure 1 , remove the non-thermal-debonding adhesive surface protective film of the thermal-debonding double-sided adhesive film, and stick the non-thermal-debonding adhesive surface to the hard glass substrate.

[0044] (4)Reference Figure 1 , remove the thermally debonding surface protective film of the thermally debonding double-sided adhesive film, and stick a flexible substrate (ITO-PEN conductive film) of the same size to the thermally debonding surface.

[0045] (5) FAI and PbI2 were dissolved in N,N-dimethylformamide in a stoichiometric ratio of 1:1 to obtain a 1 mol / L FAPbI3 perovskite precursor solution.

[0046] (6)Reference Figure 2 , using the prepared FAPbI3 perovskite precursor solution, the perovskite battery film was prepared on a flexible substrate by spin coating.

[0047] Before spin coating: Use UV-ozone instrument to treat for 20 minutes to improve the wettability of the flexible substrate so that the perovskite precursor solution can be evenly spin-coated in the subsequent spin coating step.

[0048] Spin coating: Evenly drop the prepared FAPbI3 perovskite precursor solution onto the flexible substrate, set the rotation speed to 5000 rpm, and spin for 3 seconds to obtain a uniformly dispersed perovskite wet film.

[0049] After spin coating: a flash evaporator is used to extract the solvent in the wet film, and then the extracted film is annealed at a temperature of 85° C. for 60 min to obtain a perovskite battery film.

[0050] (7)Reference Figure 3 , place the entire prepared perovskite battery film on a heating table, and set the heating temperature to 95°C; after heating for 3 minutes, the thermally debonding surface of the thermally debonding double-sided adhesive film loses its stickiness after heating, and the flexible substrate and the perovskite battery film fall off from the thermally debonding double-sided adhesive film by themselves; at this time, the flexible substrate and the perovskite battery film can be removed without stress damage to obtain a large-area flexible perovskite battery film.

[0051] Example 2

[0052] A method for obtaining a large-area flexible MAPbI3 perovskite battery film without stress damage in this embodiment includes the following steps:

[0053] (1) Clean a 4.5 cm × 4.5 cm hard glass substrate to facilitate the firm adhesion of the heat-debonding double-sided adhesive film.

[0054] (2) Prepare a heat-debonding double-sided adhesive film of the same size (Kunshan Dongzhimei Electronics Co., Ltd., foamed thermal peelable film, product number DZM-2, heating temperature of 120°C); the heat-debonding double-sided adhesive film includes a heat-debonding adhesive surface and a non-heat-debonding adhesive surface, the heat-debonding temperature of the heat-debonding adhesive surface is 120°C, and the debonding heating time is 4 minutes.

[0055] (3) Remove the protective film on the non-thermal debonding surface of the thermal debonding double-sided adhesive film, and adhere the non-thermal debonding surface to a hard glass substrate.

[0056] (4) Remove the thermal debonding surface protective film of the thermal debonding double-sided adhesive film, and adhere a flexible substrate (ITO-PET conductive film) of the same size to the thermal debonding surface.

[0057] (5) MAI and PbI2 were dissolved in N,N-dimethylformamide in a stoichiometric ratio of 1:1 to obtain a 1 mol / L MAPbI3 perovskite precursor solution.

[0058] (6) Using the prepared MAPbI3 perovskite precursor solution, the perovskite battery film was prepared on a flexible substrate by spin coating.

[0059] Before spin coating: Use UV-ozone instrument to treat for 25 minutes to improve the wettability of the flexible substrate so that the perovskite precursor solution can be evenly spin-coated in the subsequent spin coating step.

[0060] Spin coating: Evenly drop the prepared perovskite precursor liquid on the flexible substrate, set the rotation speed to 5500rpm, and the duration is 6s to obtain a uniformly dispersed perovskite wet film.

[0061] After spin coating: use a flash evaporator to extract the solvent in the wet film, and then anneal the extracted film at a temperature of 100° C. for 8 minutes to obtain a perovskite battery film.

[0062] (7) The entire prepared perovskite battery film is placed on a heating table and the heating temperature is set to 128°C. After heating for 4 minutes, the thermally debonding surface of the thermally debonding double-sided adhesive film loses its stickiness after being heated, and the flexible substrate and the perovskite battery film fall off from the thermally debonding double-sided adhesive film by themselves. At this time, the flexible substrate and the perovskite battery film can be removed without stress damage to obtain a large-area flexible perovskite battery film.

[0063] Example 3

[0064] A method for obtaining a large-area flexible CsPbI3 perovskite battery film without stress damage in this embodiment includes the following steps:

[0065] (1) Clean a 4.5 cm × 4.5 cm hard glass substrate to facilitate the firm adhesion of the heat-debonding double-sided adhesive film.

[0066] (2) preparing a heat-debonding double-sided adhesive film of the same size (Kunshan Dongzhimei Electronics Co., Ltd., foamed thermal peelable film, product number DZM-2, heating temperature of 150°C); the heat-debonding double-sided adhesive film includes two adhesive surfaces, a heat-debonding adhesive surface and a non-heat-debonding adhesive surface, the heat-debonding temperature of the heat-debonding adhesive surface is 150°C, and the debonding heating time is 5 minutes.

[0067] (3)Reference Figure 1 , remove the non-thermal-debonding adhesive surface protective film of the thermal-debonding double-sided adhesive film, and stick the non-thermal-debonding adhesive surface to the hard glass substrate.

[0068] (4)Reference Figure 1 , remove the thermally debonding surface protective film of the thermally debonding double-sided adhesive film, and stick a flexible substrate (ITO-PI conductive film) of the same size to the thermally debonding surface.

[0069] (5) CsI and PbI2 were dissolved in N,N-dimethylformamide in a stoichiometric ratio of 1:1 to obtain a 1 mol / L CsPbI3 perovskite precursor solution.

[0070] (6)Reference Figure 2 , using the prepared CsPbI3 perovskite precursor solution, the perovskite battery film was prepared on a flexible substrate by spin coating.

[0071] Before spin coating: Use UV-ozone instrument to treat for 30 minutes to improve the wettability of the flexible substrate so that the perovskite precursor solution can be evenly spin-coated in the subsequent spin coating step.

[0072] Spin coating: Evenly drop the prepared perovskite precursor liquid on the flexible substrate, set the rotation speed to 6000rpm, and the duration is 9s to obtain a uniformly dispersed perovskite wet film.

[0073] After spin coating: a flash evaporator is used to extract the solvent in the wet film, and then the extracted film is annealed at an annealing temperature of 145° C. for 5 minutes to obtain a perovskite battery film.

[0074] (7)Reference Figure 3 , place the entire prepared perovskite battery film on a heating table, and set the heating temperature to 160°C; after heating for 5 minutes, the thermally debonding surface of the thermally debonding double-sided adhesive film loses its stickiness after heating, and the flexible substrate and the perovskite battery film fall off from the thermally debonding double-sided adhesive film by themselves; at this time, the flexible substrate and the perovskite battery film can be removed without stress damage to obtain a large-area flexible perovskite battery film.

[0075] Comparative Example 1

[0076] The preparation method of a MAPbI3 perovskite battery film in this comparative example is basically the same as that in Example 2, with the main difference being that "ordinary double-sided tape" (Teflon double-sided tape, Dongguan Xinshi Packaging Materials Co., Ltd., item number 3J768) is used instead of "thermal debonding double-sided tape".

[0077] Experimental Example 1

[0078] This experimental example is used to verify the effects of "thermal debonding double-sided adhesive film" and "ordinary double-sided adhesive" on the preparation of perovskite battery thin films.

[0079] The MAPbI3 perovskite battery film was prepared according to the method of the present invention (taking Example 2 as an example) and the method of Comparative Example 1, and the peeling state and results of the perovskite battery film (together with the flexible substrate) and the double-sided adhesive were observed. Figure 4 shown.

[0080] Depend on Figure 4 It can be seen that: (1) the "ordinary double-sided adhesive" of comparative example 1 is too firmly adhered, and bending and tearing operations cannot be avoided when removing the flexible substrate, which easily causes irreversible stress damage to the perovskite battery film; (2) The "heat-debonding double-sided adhesive film" of the present invention can automatically lose its viscosity after being heated on a heating table for 3 minutes, and the flexible substrate and the perovskite battery film thereon can automatically detach from the hard glass substrate and be peeled off cleanly without any glue residue.

[0081] The above results show that this method can effectively avoid the ordinary double-sided adhesive film from sticking too tightly, causing stress damage when bending and tearing the perovskite film to be removed. The method is simple to operate, simplifies the perovskite battery film preparation process, and reduces costs.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for obtaining a large-area flexible perovskite battery film without stress damage, characterized in that: The steps include: (1) selecting a suitable thermally debonded double-sided adhesive film according to the required annealing temperature of the perovskite; the thermally debonded double-sided adhesive film comprises two adhesive surfaces, a thermally debonded adhesive surface and a non-thermal debonded adhesive surface; (2) adhering the non-thermal debonding adhesive surface of the thermal debonding double-sided adhesive film to a hard glass substrate; (3) pasting the flexible substrate onto the heat-loss adhesive surface of the heat-loss adhesive film; (4) dissolving AX and BX2 in N,N-dimethylformamide at a stoichiometric ratio of 1:1 to obtain a perovskite precursor solution; (5) Preparing a perovskite battery film on a flexible substrate using the prepared perovskite precursor solution; (6) The entire prepared perovskite battery film is heated, and the heat-debonding adhesive surface of the heat-debonding double-sided adhesive film loses its adhesiveness due to the heat, and the perovskite battery film is removed from the hard glass substrate.

2. The method for obtaining a large-area flexible perovskite battery film without stress damage according to claim 1, characterized in that: In the step (1), the selection criteria of the thermal debonding double-sided adhesive film is: the thermal debonding temperature of the thermal debonding adhesive surface is higher than the annealing temperature required for the perovskite.

3. The method for obtaining a large-area flexible perovskite battery film without stress damage according to claim 1, characterized in that: In the step (1), the thermal debonding double-sided adhesive film is specifically selected from a foamed thermal debonding double-sided adhesive film, the thermal debonding temperature is 90 to 150° C., and the debonding heating time is 3 to 5 minutes.

4. The method for obtaining a large-area flexible perovskite battery film without stress damage according to claim 1, characterized in that: In the step (3), the flexible substrate is one of ITO-PEN, ITO-PET, and ITO-PI conductive films.

5. The method for obtaining a large-area flexible perovskite battery film without stress damage according to claim 1, characterized in that: In the step (4), A is one or more of formamidinium ion, methylamine ion, and cesium ion; B is one or more of lead ion, tin ion, manganese ion, germanium ion, and copper ion; and X is one or more of chloride ion, iodide ion, and bromide ion.

6. The method for obtaining a large-area flexible perovskite battery film without stress damage according to claim 1, characterized in that: In the step (5), a large-area perovskite battery film is prepared by spin coating.

7. The method for obtaining a large-area flexible perovskite battery film without stress damage according to claim 6, characterized in that: The specific operation of preparing a large-area perovskite battery film by spin coating is as follows: Before spin coating: use UV-ozone instrument to treat for 20-30 minutes; Spin coating: evenly drop the prepared perovskite precursor solution on the flexible substrate, set the rotation speed to 5000-6000rpm, and the duration is 3-9s to obtain a uniformly dispersed perovskite wet film; After spin coating: use a flash evaporator to extract the solvent in the wet film, and then anneal the extracted film at a temperature of 85 to 145° C. for 5 to 60 minutes to obtain a perovskite battery film.

8. The method for obtaining a large-area flexible perovskite battery film without stress damage according to claim 1, characterized in that: In the step (6), the entire prepared perovskite battery film is placed on a heating table, and the heating temperature is set to be 5 to 10°C higher than the thermal debonding critical temperature of the thermal debonding double-sided adhesive film; the thermal debonding adhesive surface of the thermal debonding double-sided adhesive film loses its viscosity after being heated, and the perovskite film together with the flexible substrate is removed from the hard glass substrate, thereby obtaining the desired large-area flexible perovskite battery film.